ADSORPSI ION FOSFAT OLEH LEMPUNG TERAKTIVASI ASAM SULFAT (H2SO4) - Ida Norma Sinta; Putu Suarya; Sri Rahayu Santi (Jurnal Kimia (Journal of Chemistry), 2015)
Activated clay can be used as an adsorbent to adsorb phosphate ions in solution. The aims of this research are to study the characteristics of the clay before and after activated (covering the surface acidity, surface area and basal spacing) and to study the adsorption capacity of activated clay to phosphate solution. The results showed, the activated clay gave surface acidity of 0.7202 mmol/g and 2.0018 mmol/g, surface area of 12.6602 m2/g dan 25.6101 m2/g, and d-spacing of montmorillonite was d (Å) = 0.12. The optimum condition for phosphate adsorption by this clay was found at 15 minutes contact time, pH 3, and  concentration of 70 ppm yielding phosphate adsorption capacity of 3.0349 mg/g following the Langmuir isotherm.